Efektivitas Penerapan Terapi Musik Mozart (Violin Concerto) Terhadap Nyeri Haid Primer - Yohana Bila Rangga; Sirli Mardianna Trishinta; Arie Jefry Ka’arayeno (Nursing News : Jurnal Ilmiah Keperawatan, 2021)
Menstrual pain is a symptom that occurs when hormone progesterone in the body is in balanced which can relief with classical music therapy. The purpose of this study was to determine the effect of Mozart music therapy on primary menstrual pain in students of the nursing Program at Tribuwana Tunggadewi University Malang. The research Science design used one-group pre-post test design. Samples are Student of Nursing Science program of UNITRI bortch 2020 which experienced menstrual used or primary menstrual pain amounted 30 people. Data collecting used purposive sampling. Instrument research used by observation level pain or NRS (numerical rating scale). Data analyzed by Marginal Homogeneity Test. The result of the study prove almost half the of student of nursing science program at tribhuwana tunggadewi university malang batch 2020 said the experienced level of primary menstruasi pain are very severe and most of them experienced severe  level of paint. The result of marginal homogeneity test obtained ñvalue: (0,000) (0,005) so that there is on effect of therapy classical music mozart against primary menstrual pain on Student of Nursing Science Program At Tribhuwana Tunggadewi University Malang. Batch 2020. Based on this research, it is hoped that further researchers can ensure other factors that reduce the level of primary menstrual pain